Calixarene-decorated liposomes for intracellular cargo delivery. Issue 30 (16th July 2021) - Morbioli, Ilaria; Casnati, Alessandro; Esko, Jeffrey D.; Tor, Yitzhak; Sansone, Francesco
Abstract : Liposomes equipped at the outer membrane with positively charged calixarenes show improved efficiency in cargo delivery. This is facilitated by the interaction between the macrocycle units and heparan sulfate proteoglycans surrounding the cell. Abstract : Amphiphilic calix[4]arenes, functionalized with guanidinium groups, are used to decorate the outer surface of liposomes and significantly improve the cellular uptake of a cargo compared to plain liposomes. The improved uptake is elicited and mediated by the interaction between the cationic polar heads of the macrocycle units embedded in the liposome bilayer and anionic heparan-sulfate proteoglycans surrounding the exterior of cells.